Penguatan Kapasitas Aparatur Desa dalam Pengelolaan Konten Website Melalui Program Pelopor Informasi dan Digitalisasi Desa di Lombok Barat - Ummah, Athik Hidayatul; Dwi Ayu Oktaviara; Abdul Hamid (Tasnim Journal for Community Service, 2024)
The purpose of this service is to strengthen the capacity of village officials as content managers of village websites. The village information and digitalization pioneer program aims to introduce the village more widely as well as a medium for information disclosure. This service method uses the ABCD (Asset Based Community Development) approach which focuses on aspects of village community empowerment through the utilization of assets and potential to improve the quality of life of the community. The two villages that became the focus of the service were Jembatan Gantung village and East Mareje village in the Lembar sub-district of West Lombok. This service activity produced a number of important and interesting findings, namely: First, the two villages that are the focus of the service have the potential of natural resources and human resources that need to be developed. Second, the website is one of the media that can be managed easily as a representation of the village in the digital world. The village website has a role as an information center, improving community resources, promotional media and village development. Third, capacity building of village officials as website content managers needs to be improved to build the sustainability of the program. Fourth, the website needs to be managed in a solid team and designed in creative and interesting ways so that people like to access it. The key is in the quantity and quality of the content and media display of the website.